A sodium hyposulfite fuel cell for efficient Cr(VI) removal. (May 2022) - Wang, Dongfang; Zong, Zhiqiang; Ye, Jinghong; Wu, Qingchuan; Zhang, Xiaojiang; Wu, Zhengyan; Zhang, Jing; Xu, He; Cai, Dongqing
Abstract: This work shows a strategy of reducing hexavalent chromium (Cr(VI)) by sodium hyposulfite (Na2 S2 O3 ) with self-generated electricity via a dual-chamber non-biological fuel cell (D-nBFC). Therein, Na2 S2 O3 was electro-oxidized on graphite felt (GF) at anode and Cr(VI) in strong acidic solution was electro-reduced at GF/CCP cathode (GF decorated with conductive carbon paint (CCP)). Additionally, an agar salt bridge, consisting of saturated KCl solution, was introduced to form complete circuit by offering ions. The results showed that Cr(VI) was reduced to trivalent chromium (Cr(III)) and the D-nBFC system could produce electricity in this process. This system could obtain a high Cr(VI) removal efficiency (97.0%), 110 μA maximum current, and 13.4 mW m −2 maximum power density in 4 h. In addition, the proposed system had high reusability after five cycles and the relative standard deviation was only 3.4% ( n  = 5). Thus, this D-nBFC system provides a promising and eco-friendly method for treatment of Cr(VI) pollution and generating electricity simultaneously, and also has potential application value for other heavy metals remediation. Graphical abstract: Image 1 Highlights: A dual-chamber non-biological fuel cell (D-nBFC) was constructed to reduce Cr(VI). This D-nBFC system could generate electricity without energy consumption. Sodium hyposulfite in anode was as electron donator to reduce Cr(VI) in cathode. The cathode material (GF/CCP) had high reusability after five cycles.